PENERAPAN KODE ETIK JURNALIS TELEVISI INDONESIA PADA PROGRAM BERITA KRIMINAL DI RIAU TELEVISI - Rusdiyanto, Rusdiyanto; Cahyadi, Yan; Siregar, Helly Aroza (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
The purpose of this study was to determine and analyze whether the criminal news broadcast on the Detak Riau News program on Riau Television was in accordance with the The Ethics Code of Indonesian Television Journalist. The method used is quantitative content analysis by analyzing the coding results and then describing it descriptively. The results of the study indicated that the criminal news in a complete and actual category.Iin general the criminal news program did not show sadistic shows, although there were still some news that broadcast sadism, but the percentage was small. This criminal news program can be said to have met the ethics of the politeness aspect of the news that displays vulgar impressions and break the human rights, although there were news that still display minimal clothing and violence, but with a small percentage. Furthermore, in terms of the identity of the perpetrators and suspects in immoral news, this criminal news program had fully complied with the code of ethics.